2012
DOI: 10.1089/cap.2011.0129
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aripiprazole on Electrocardiography in Children with Pervasive Developmental Disorders

Abstract: To our knowledge, this is the first systematic evaluation of the cardiac effects of aripiprazole in children and adolescents. The results are consistent with previously published literature in adults that aripiprazole has no significant cardiac effects and can be deemed a low risk for causing sudden death. It will be important to confirm these findings in a randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 46 publications
0
14
0
2
Order By: Relevance
“… 36 , 37 , 86 One prospective, open-label study (n=25; age range: 5–17 years) investigated aripiprazole use for treating irritability in cases of Asperger’s disorder and pervasive developmental disorder not otherwise specified, and found no significant changes in the PR, QRS, RR, and QTc intervals after 14 weeks of aripiprazole therapy. 88 The posttreatment QTc values were all below 440 ms, and the administered dosage was not significantly correlated with the percent change in QTc. 88 These results suggest that aripiprazole does not significantly impact cardiac health and carries a low risk of causing sudden death.…”
Section: Aripiprazole Safety Data In Children and Adolescentsmentioning
confidence: 85%
See 1 more Smart Citation
“… 36 , 37 , 86 One prospective, open-label study (n=25; age range: 5–17 years) investigated aripiprazole use for treating irritability in cases of Asperger’s disorder and pervasive developmental disorder not otherwise specified, and found no significant changes in the PR, QRS, RR, and QTc intervals after 14 weeks of aripiprazole therapy. 88 The posttreatment QTc values were all below 440 ms, and the administered dosage was not significantly correlated with the percent change in QTc. 88 These results suggest that aripiprazole does not significantly impact cardiac health and carries a low risk of causing sudden death.…”
Section: Aripiprazole Safety Data In Children and Adolescentsmentioning
confidence: 85%
“… 88 The posttreatment QTc values were all below 440 ms, and the administered dosage was not significantly correlated with the percent change in QTc. 88 These results suggest that aripiprazole does not significantly impact cardiac health and carries a low risk of causing sudden death.…”
Section: Aripiprazole Safety Data In Children and Adolescentsmentioning
confidence: 85%
“…Furthermore, the QTc interval showed a significant shortening after switching from OLZ to ARP (Suzuki et al ., ). In children with pervasive development disorders, ARP treatment did not change the QTc interval (Ho et al ., ). Our results are consistent with those of the three studies.…”
Section: Discussionmentioning
confidence: 97%
“…Aripiprazole has not been associated with significant QTc interval prolongation or other abnormal ECG findings in children with ASD. 111 Other atypical antipsychotics have not been as thoroughly investigated in children with autism, and the studies have typically yielded mixed results. Two small open-label trials of olanzapine reported high response rates (6/7 and 5/6 participants), 112,113 though results from an additional two studies were less robust (3/25 participants and 12/40 participants were responders).…”
Section: Atypical Antipsychoticsmentioning
confidence: 99%